2009
DOI: 10.1080/09637480802495297
|View full text |Cite
|
Sign up to set email alerts
|

Cooking does not decrease hydrophilic antioxidant capacity of wild blueberries

Abstract: The present study examined the effects of domestic cooking methods on the hydrophilic antioxidant activity (HAA) of wild blueberries. Baked, microwaved, simmered, and pan-fried frozen wild blueberries, and a thawed uncooked control, were analyzed for HAA using an ABTS/H(2)O(2)/HRP decoloration method. All cooking treatments were derived from recipes using wild blueberries, and were performed in triplicate. A randomized block design was used to determine whether there were statistical differences in antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…In addition, heating fruits in a microwave oven increased temperature faster than other heating methods 25 . This destroyed cell membranes of wild blueberries (Vaccinium angustifolium) and allowed antioxidants to be easily extracted from the fruits 26 . Our result agrees with Chuah et al 24 who reported that cooking peppers by microwaving had more antioxidants than stir-frying and boiling.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, heating fruits in a microwave oven increased temperature faster than other heating methods 25 . This destroyed cell membranes of wild blueberries (Vaccinium angustifolium) and allowed antioxidants to be easily extracted from the fruits 26 . Our result agrees with Chuah et al 24 who reported that cooking peppers by microwaving had more antioxidants than stir-frying and boiling.…”
Section: Resultsmentioning
confidence: 99%
“…Other reports of increased phytochemicals associated with culinary preparations include increased quercetin concentrations in onions (Allium cepa L.) exposed to sautéing, baking or boiling [21], and enhanced absorption of lycopene in tomatoes exposed to heat [22]. Moreover, a previous study suggests that hydrophilic antioxidant activity of wild blueberries is not negatively impacted by a variety of domestic cooking methods and is even increased in pan-fried frozen WBB [23]. Kalt et al [24] determined that WBB products varied significantly in antioxidant capacity and that higher levels of ANC and total phenolics were present in WBB that were pureed at 60 • C compared to those at 20 • C [24].…”
Section: Controlmentioning
confidence: 99%
“…This has to be taken into account in active packaging because migration from food contact materials is not negligible, even the concentration of migrants in the food can approach that of substances used as direct food additives (SimalGándara, Damant, & Castle, 2002). Great interest has recently been shown in natural products because of the numerous benefits to health, such as the antioxidant effects of tea, rosemary, oregano, spices, herbs, clove, blueberries, mustard, red wine and others (Alén-Ruiz, García-Falcón, Pérez-Lamela, Martínez-Carballo, & Simal-Gándara, 2009;Beddows, Jagait, & Kelly, 2000;Bhale, Xu, Prinyawiwatkul, King, & Godber, 2007;Houhoula, Oreopoulou, & Tzia, 2003;McCarthy, Kerry, Kerry, Lynch, & Buckley, 2001;Murphy, Renfroe, Brevard, Lee, & Gloeckner, 2009;Wanasundara & Shahidi, 1998).…”
Section: Introductionmentioning
confidence: 98%